Prevalence of serum markers of hepatitis B and C in blood donors and pregnant women in Algeria - Ayed, Z.; Houinato, Dismand; Hocine, M.; Ranger-Rogez, S.; Denis, François (My University, 1995)
Serologic markers of hepatitis B (AgHBs, anti-HBc) and hepatitis C (anti-HCV) are investigated in 1,112 apparently healthy blood donors and 715 pregnant women in Algeria. Data of this study have shown a low prevalence of HCV and confirm that this country belongs to the middle endemic area for HBV. Indeed the anti-HCV were detected in 0.18 % of blood donors and 0.19 % of pregnant women. The AgHBs were observed in 3.6 % of blood donors and 1.6 % of pregnant women, anti-HBc antibodies were found in 13 % of blood donors and 11.1 % of pregnant women.
Keywords: Prevalence; serum markers; hepatitis B and C; pregnant women; Algeria]